Digital rockets: Resisting necropolitics through defiant languaging and artivism. (October 2022) - Silva, Daniel; Maia, Junot
Abstract: This article draws from our ethnography in the Complexo do Alemão favelas (neighborhoods built by residents) in Rio de Janeiro to discuss how Black activists bring affordances of digitalization and enregistered practices into broader arenas of political participation. We unpack our own positionality and experience with the armed surveillance and securitization of normative regimes that challenge (and often cooperate with) the state in governing peripheral and, to a lesser extent, central areas in Brazilian cities. Favela residents are disproportionately affected by these violent forms of securitization. We look to their ordinary digital and enregistered languaging and 'artivism' as a means of surviving necropolitics that are proper to the African diaspora. In dialogue with the sociolinguistics of globalization and the sociology of violence, the study provides ethnographic evidence of situated cooperation and creative use of language and technologies. We believe this may offer promising paths for further objectives, including antiracist education and comparative studies of grassroots activism.